18S rRNA, a potential reference gene in the qRT-PCR measurement of bisphenol A contamination in green mussels (Perna viridis) collected from the Gulf of Thailand - Boonphakdee, Chuta; Ocharoen, Yhardpeth; Shinn, Andrew P.; Suanla, Santi; Thamnawasolos, Jeeranan (Agriculture and Natural Resources, 2019)
Normalization of reference genes through the selection of appropriate housekeeping genes is important for the reliable quantification of mRNA analyzed using real-time polymerase chain reaction (qRT-PCR). The suitability of various housekeeping genes (HKGs), were valuated as internal references to verify the levels of the contaminant bisphenol A (BPA, 2,2-bis (4-hydroxyphenyl) propane) by determining the level of gene expression of cytochrome P450 4 (cyp4) within the digestive gland of green mussels (Perna viridis)—a species used for biomonitoring environmental levels. Additionally, the effect was explored of mussel gender and maturity status (juvenile or mature) on the stability of the expression of the reference genes. Three candidate HKGs were examined, namely 18S rRNA, 28S rRNA and β-actin. The expression stability was calculated using three statistical approaches—NormFinder, BestKeeper and a comparative threshold cycle (Ct) method. The study found that of the three candidate reference genes, 28S rRNA and 18S rRNA were the most stable with no significant differences when maturity, gender and exposure to BPA were considered. It was noted that when these genes (18S rRNA, 28S rRNA, β-actin) were used for normalization using animals exposed to 10 ng BPA and the qRT-PCR method, different levels of cyp4 expression were observed. However, BPA significantly decreased the expression levels of cyp4 compared to the control (animals not exposed to BPA), only when 18S rRNA was used as an internal reference. These results highlighted the importance of selecting appropriate reference genes as the endogenous control in qRT-PCR in biomonitoring programs of BPA.